Ragam Pendekatan Dalam Pengembangan Kurikulum Pendidikan Agama Islam (PAI) - Dewi Puspita Sari; Nur Aisyah; Muhammad Abdurrohman; Mustafiyanti Mustafiyanti (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The curriculum is an important part of the education system because it is one of the determining factors in achiefing goals. Likewise, the Islamic religious education (PAI) curriculum also plays a central role in various curricula to achieve the direction and goals of Islamic education itself. Islamic education aims to develop all human potential based on Islamic law. However, in reality, the PAI curriculum still has problems in real life. For example, the education model is still docmatic, old-fashioned, redundant, and the religius concept taught are no longer relevant to modern life. Teachers and all scool staff mus be able to trully understand and design the curriculum. In developing an Islamic religious education (IRE) curriculum, a special approach is anneded that ensures that the designed curriculum can bring students to the desiret changes. Teachers can choose several approaches that suit their teatching model, taking into account the specifics of Islamic education itself. Four approaches can be used in curriculum development: academic, humanistic, technological and social reconstruction approaches. The developed curriculum can then be used by various PAI teachers in the teaching and learning process at school.